SANITARY IMAGINARY IN MENDOZA AT THE END OF THE XIX CENTURY: HYGIENE AND SANITATION WORKS DURING THE INTENDANCE OF LUIS LAGOMAGGIORE (1884 - 1888) - Raffa, Cecilia (Revista de Historia Social y de las Mentalidades, 2011)
The discovery of the illness like social problem wa s part of the "urban ideology"  articulated in lathe of the progress, the order, th e hygiene and the well-being, starting from  the second half of the XIX century. The wrongs bega n to attract the attention of the leaders  and it is there where the hygiene (urban and human) he/she begins to take importance like  preventive intervention instrument and at the same  time disciplinarian, becoming partly of  the progress and the civilization.  The practical hygienist and the imaginary ones in l athe of her, they reduced the  urban problems to the merely sanitary and moral one s until the first decades of the XX  century. That was the case of Mendoza and its "Neig hborhood of the Ruins."  The colonial city transformed into periphery after  the earthquake of 1861, remained  full with brashes until initiate the decade of the  '80. it is the vision hygienist of century  ends, the one that modifies the government's attitu de that began to see the danger that was  to have an area degraded near the New City. In that action line it is Luis Lagomaggiore.  We will attempt in this work to relate government's actions with the images in lathe  of the hygiene. In this case, the hygiene of the "o ther": the inhabitant of the suburbs  represented in the Neighborhood of the Ruins.
Keywords: Imaginary; hygiene; XIX century; it works public